Endurance exercise training up-regulates lipolytic proteins and reduces triglyceride content in skeletal muscle of obese subjects - Louche, Katie; Badin, Pierre-Marie; Montastier, Emilie; Laurens, Claire; Bourlier, Virginie; de Glisezinski, Isabelle; Thalamas, Claire; Viguerie, Nathalie; Langin, Dominique; Moro, Cedric (The journal of clinical endocrinology and metabolism, 2013)
Skeletal muscle lipase and intramyocellular triglyceride (IMTG) play a role in obesity-related metabolic disorders. The aim of the present study was to investigate the impact of 8 weeks of endurance exercise training on IMTG content and lipolytic proteins in obese male subjects. Ten obese subjects completed an 8-week supervised endurance exercise training intervention in which vastus lateralis muscle biopsy samples were collected before and after training. Clinical characteristics and ex vivo substrate oxidation rates were measured pre- and posttraining. Skeletal muscle lipid content and lipolytic protein expression were also investigated. Our data show that exercise training reduced IMTG content by 42% (P < .01) and increased skeletal muscle oxidative capacity, whereas no change in total diacylglycerol content and glucose oxidation was found. Exercise training up-regulated adipose triglyceride lipase, perilipin (PLIN) 3 protein, and PLIN5 protein contents in skeletal muscle despite no change in mRNA levels. Training also increased hormone sensitive-lipase Ser660 phosphorylation. No significant changes in comparative gene identification 58, G₀/G₁ switch gene 2, and PLIN2 protein and mRNA levels were observed in response to training. Interestingly, we noted a strong relationship between skeletal muscle comparative gene identification 58 and mitochondrial respiratory chain complex I protein contents at baseline (r = 0.87, P < .0001). Endurance exercise training coordinately up-regulates fat oxidative capacity and lipolytic protein expression in skeletal muscle of obese subjects. This physiological adaptation probably favors fat oxidation and may alleviate the lipotoxic lipid pressure in skeletal muscle. Enhancement of IMTG turnover may be required for the beneficial metabolic effects of exercise in obesity.